On-the-move measurement analysis for Ka-band high throughput satellite and LiFi communication networks in tropical region - Kalaivaanan, P. M.; Sali, Aduwati; Raja Abdullah, Raja Syamsul Azmir; Yaakob, Syamsuri; Jit Singh, Mandeep; Al-Saegh, Ali M. (Institute of Electrical and Electronics Engineers, 2021)
With the point in evaluating the performance of the On-the-Move (OTM) Satellite Communication and Light Fidelity (SatCom-LiFi), an extensive study of measurement has been conducted to give a wide vision of the SatCom-LiFi potential under a tropical region. As the interest for OTM network connectivity to offload the C-band capacity arises due to frequency spectrum scarcity, satellite networks offer to balance topographical requirements under tropical environment as the Next Generation Networks (NGN) trend for OTM communication system solutions. To date, mobile satellite terminal propagation model was carried out at temperate regions where further experimental measurement is needed under the OTM scenario in tropical region. This paper discusses on the areas where there are limited real-time data under the OTM scenario (e.g. rain attenuation, power arch) at Ka-band frequency. Integration infers, to be specific, the use of new elements capable in providing performance analysis of all systems involved and to take possible decision, in determining the need for a technically feasible solution. Measurement results reveal that, throughput data rate of 15 Mbps were able to be delivered for more than 80% of the time under the speed of 150 km/h with shielded mesh antenna. In addition to that, this paper reveals the favorable circumstances and inadequacies of OTM network quality, in which the measurement presented plays an important role for future researchers in distinguishing highly accurate predictions.